The role of gasotransmitter hydrogen sulfide in plant cadmium stress responses - Yu, Yan; Fotopoulos, Vasileios; Zhou, Kejin; Fernie, Alisdair R. (My University, 2025)
Cadmium (Cd) is a toxic heavy metal that poses a significant risk to both plant growth and human health. To mitigate or lessen Cd toxicity, plants have evolved a wide range of sensing and defense strategies. The gasotransmitter hydrogen sulfide (H2S) is involved in plant responses to Cd stress and exhibits a crucial role in modulating Cd tolerance through a well-orchestrated interaction with several signaling pathways. Here, we review potential experimental approaches to manipulate H2S signals, concluding that research on another gasotransmitter, namely nitric oxide (NO), serves as a good model for research on H2S. Additionally, we discuss potential strategies to leverage H2S-reguated Cd tolerance to improve plant performance under Cd stress.
Keywords: signaling network; cadmium stress; hydrogen sulfide; persulfidation